2005
DOI: 10.1590/s0103-84782005000200039
|View full text |Cite
|
Sign up to set email alerts
|

Substratos na emergência de plântulas e expressão da poliembrionia em porta-enxertos de citros

Abstract: Este experimento objetivou testar a influência de substratos sobre a velocidade de emergência de plântulas e a poliembrionia de porta-enxertos cítricos. O experimento foi conduzido em casa-de-vegetação utilizando-se sementes de quatro porta-enxertos cítricos (Trifoliata, Citrange ‘Troyer’, Citrumelo ‘Swingle’ e Limoeiro ‘Cravo’) semeadas em 20 tubetes cônicos de 50 cm³. Nas sub-parcelas foram testados três substratos comerciais (Substratos MogimaxÒ, Plug MixÒ e Cruz AltaÒ) e um substrato misto (casca de arroz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
1
2
0
4
Order By: Relevance
“…1 notes the characteristics: emergence percentage and emergence rate index, the Rangpur lime rootstock does not differ from lemon Volkameriano, but these differ statistically from Trifoliate orange, 'Swingle' citrumelo and Flying Dragon, which do not differ when evaluated 60 days after sowing (DAS). These results are partly similar to those found by Schafer et al (2005), who observed that the Rangpur lime rootstock has higher emergence rate index in relation to rootstock P. trifoliata orange and 'Swingle' citrumelo, however, these do not differ. In regards to the dry mass of the root, there is only a significant difference between the rootstock 'Swingle' citrumelo and Rangpur lime.…”
supporting
confidence: 90%
“…1 notes the characteristics: emergence percentage and emergence rate index, the Rangpur lime rootstock does not differ from lemon Volkameriano, but these differ statistically from Trifoliate orange, 'Swingle' citrumelo and Flying Dragon, which do not differ when evaluated 60 days after sowing (DAS). These results are partly similar to those found by Schafer et al (2005), who observed that the Rangpur lime rootstock has higher emergence rate index in relation to rootstock P. trifoliata orange and 'Swingle' citrumelo, however, these do not differ. In regards to the dry mass of the root, there is only a significant difference between the rootstock 'Swingle' citrumelo and Rangpur lime.…”
supporting
confidence: 90%
“…Para Schaffer et al (2005) a escolha do tipo de substrato é importante tanto para a propagação vegetativa quanto por sementes e constitui um dos fatores de maior influência no enraizamento de estacas, pois além de sustentá-las, mantém a base úmida, aerada e protegida da luz. Sendo que estes fatores podem variar em função do material utilizado (WAGNER JÚNIOR et al, 2006).…”
Section: Resultsunclassified
“…En este caso, la obstrucción en el sitio de la malformación puede disminuir el transporte, aun cuando el agua del suelo no sea limitante. El aumento en área foliar implica mayor área de incidencia de radiación, y por lo tanto mayor transpiración y fotosíntesis (Pire et al, 2007). En este caso, las plantas no están respondiendo a una condición del ambiente, sino a una limitación propia.…”
Section: Discussionunclassified
“…We have found differences in the degree of polyembryony, germination percentage (Shinde et al, 2007), plant vigor (leaf area and height), leaf nutrient content, water relations (Shãfer et al, 2005), flooding and drought stress resistance (García-Sánchez et al, 2007), hydraulic conductivity, root length, transpiration and salt stress conditions (Castle et al, 2009;Gimeno et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation